Utilization of plants as dyes and natural color binder in Traditional Pringgasela Woven Fabric, East Lombok, West Nusa Tenggara, Indonesia - Mulyati Rahayu; Emma Sri Kuncari; Himmah Rustiami; Dewi Susan (Society for Indonesian Biodiversity, 2020)
Abstract. Rahayu M, Kuncari ES, Rustiami H, Susan D. 2020. Utilization of plants as dyes and natural color binder in traditional Pringgasela woven fabric, East Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 21: 636-641. Since earlier times, dye has an important role in human life, especially related to the ritual practice. Mineral material was first used as natural dyes. In order to inventory the uses of plants as a dye and natural color binder by the local community of Pringgasela, ethnobotany research was done. This research had been done by interviewing the